Transportation, Storage, and Disposal of Radioactive Materials 2003
DOI: 10.1115/pvp2003-2140
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Behavior of Alloy 22 in Calcium Chloride and in Calcium Chloride Plus Calcium Nitrate Brines

Abstract: Alloy 22 (UNS N60622) is a nickel-based alloy, which is extensively used in aggressive industrial applications, especially due to its resistance to localized corrosion and stress corrosion cracking in high chloride environments. The purpose of this work was to characterize the anodic behavior of Alloy 22 in concentrated calcium chloride (CaCl2) brines and to evaluate the inhibitive effect of nitrate, especially to localized corrosion. Standard electrochemical tests such as polarization resistance and cyclic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…13 Before mounting them onto the metallic specimens, the CF were covered with PTFE tape to ensure a tight crevicing gap. [14][15][16] The specimens had a ground finish of 600grit paper. There are two types of specimens mentioned in this work: (1) The as-received wrought mill annealed (MA) and (2) the solution heat-treated (MA + SHT) which were annealed in air for 20 min at 1121°C and then water quenched.…”
Section: Methodsmentioning
confidence: 99%
“…13 Before mounting them onto the metallic specimens, the CF were covered with PTFE tape to ensure a tight crevicing gap. [14][15][16] The specimens had a ground finish of 600grit paper. There are two types of specimens mentioned in this work: (1) The as-received wrought mill annealed (MA) and (2) the solution heat-treated (MA + SHT) which were annealed in air for 20 min at 1121°C and then water quenched.…”
Section: Methodsmentioning
confidence: 99%
“…al. found that in potentiodynamic testing of Alloy 22 in 5 M calcium chloride (CaC12) solutions, the onset of localized corrosion could be shifted from 7S°C to 105OC by adding 0.5 M calcium nitrate (~a(N03)2).~ AS the ratio of nitrate to chloride is increased, an increase in both breakdown potentials and repassivation potentials occurs, and the difference between these potentials and open circuit values increases. 2,3,7,11 In this study the effect of nitrate on localized corrosion of welded Alloy 22 specimens at extremes of chloride concentration and temperature in CaCI2 + Ca(N03)2 solutions was examined.…”
mentioning
confidence: 99%
“…[8][9][10][13][14][15] The presence of nitrate (NO 3 -) and other oxyanions in the solution minimizes or eliminates the susceptibility of Alloy 22 to crevice corrosion. [8][9][10][16][17][18][19][20][21][22][23] The value of the ratio R (R = [NO 3 -]/([Cl -]) has a strong effect of the susceptibility of Alloy 22 to crevice corrosion. [16][17][18][19][20][21][22][23] The higher the nitrate to chloride ratio the stronger the inhibition by nitrate.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] The combined presence of Cr, Mo and W imparts Alloy 22 with high resistance to localized corrosion such as pitting corrosion and stress corrosion cracking even in hot high chloride (Cl -) solutions. [7][8][9][10][11][12] Alloy 22 may suffer localized corrosion such as crevice corrosion when it is anodically polarized in chloride containing solutions. [8][9][10][13][14][15] The presence of nitrate (NO 3 -) and other oxyanions in the solution minimizes or eliminates the susceptibility of Alloy 22 to crevice corrosion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation